Street Addressing and the Management of Cities - Farvacque-Vitkovic, Catherine; Godin, Lucien; Leroux, Hugues; Verdet, Florence; Chavez, Roberto (Washington, DC: World Bank, 2012)
This book reviews the role of addressing within the array of urban management tools and explores the links between addressing and civic identity, urban information systems, support to municipal services, tax systems, land management and tenure issues, slum upgrading, support to concessionary services, and economic development. It outlines current and future applications, highlights practices in many African countries, and offers a methodological guide for implementing street addressing initiatives which is widely applicable in other parts of the world.